DEEPENING THE INTEREST OF ONLINE GAMES LEARNER AS AN EFFORTS TO FIND NEW PATTERNS IN LEARNING ENGLISH (Case Study on English Subject I in the UBSI Faculty of Information Technology Accounting Information System Class) - Mursyid Kasmir Naserly (Universitas Singaperbangsa Karawang, 2019)
This research was conducted as an effort to produce an unusual pattern of learning English. Developing the pattern the researcher embodies in the form of searching the learner's interest in English, after that the researcher observes each activity related to that interest to find a new formula in learning English, especially at the elementary level. Interest in this research is focused on a student who likes playing online games, and then researchers try to explore it through the interview method so that the expected formula can be summarized in detail and can be applied in Basic English learning patterns in general, according to the interests of each learner.